Regioselective alkane oxygenation with H2O2 catalyzed by titanosilicalite TS-1 - Shul’pin, Georgiy B.; Sooknoi, Tawan; Romakh, Vladimir B.; Süss-Fink, Georg; Shul’pina, Lidia S. (My University, 2006)
Titanosilicalite TS-1 catalyses oxidation of light (methane, ethane, propane and n-butane) and normal higher (hexane, heptane, octane and nonane) alkanes to give the corresponding isomeric alcohols and ketones. The oxidation of higher alkanes proceeds in many cases with a unique regioselectivity. Thus, in the reaction with n-heptane the CH2 groups in position 3 exhibited a reactivity 2.5 times higher than those of the other methylene groups. This selectivity can be enhanced if hexan-3-ol is added to the reaction mixture, the 3-CH2/2-CH2 ratio becoming 10. It is assumed that the unusual selectivity in the oxidation of n-heptane (and other higher alkanes) is due to steric hindrance in the catalyst cavity. As a result, the catalytically active species situated on the catalyst walls can only easily react with certain methylenes of the alkane, which is adsorbed in the cavity taking U-shape (hairpin) conformations.
Keywords: alkanes; catalysis; hydrogen peroxide; nano-chemistry; regioselectivity; titanium; titanosilicalite TS-1; oxygenation